Aplicação dos processos de separação com membranas e adsorção em carvão ativado no tratamento de efluentes da indústria têxtil - Ströher, Ana Paula (2014)
The scarcity of natural resources has led to increasingly strict environmental laws, and the costs involved with the use of these resources has become increasing in all industrial sectors. In Brazil, the textile sector has a great importance in the national and regional economy. The concern of this sector is the major consumer of water, raw materials and dyes and consequently of considerable quantities of waste generated. Such effluent is highly polluting due to the presence of dyes which are not fixed to the fibers and auxiliary products used during the processing of the fabric. Thus, this study presents an evaluation of two methods of treatment of textile effluent, membrane separation and adsorption, combined with a pre-treatment by coagulation/flocculation/sedimentation for removal of pollutants from effluent of an industrial laundry and possible reuse of water in the wash process of the fabrics. To this end, high rates of removal of compounds present in the effluent, especially those which relate to the parameters of color, turbidity, organic matter are required. The first step of this work was to evaluate the efficiency of pretreatment by coagulation/flocculation/sedimentation for four different coagulants: aluminum poly (PAC), aluminum sulfate, moringa and tannin. First we determined the optimum dosage of coagulant and the results of this step were 0,4 mL/L for CAP, 400 mg/L aluminum sulfate, 1600 mg/L for the jug and 100 mg/L tannin. Moringa and aluminum sulfate in addition to require higher dosages in the treatment of effluent study showed lower efficiency. The best results were obtained for the PAC and tannin. Reductions color, turbidity and COD were respectively 92,8%; 96,6% and 70,3% for CAP and 95,2%; 98,4% and 60,5% for tannin. Tannin, because it is a natural coagulant, proved a good alternative option for the treatment of the effluent under study. Subsequently, the performance of the separation process combined with each of the membranes pretreatment coagulation/flocculation/sedimentation was studied. Tubular ceramic membranes were used with pore diameters of 0,01 to 0,1 ?m. The operating conditions used in the process with membranes were: pressure of 1,0 and 2,0 bar and temperature 30 °C. The results of this step showed that the lowest values of color, turbidity and COD were obtained for the membrane of 0,1 ?m and 1,0 bar for the pre-treatment with CAP and tannin. The third step consisted in the study of adsorption on activated carbon. For the first batch process we evaluated the effect of pH and particle size of the adsorbent where it was found that at pH 4 the largest occurring color removal and the particle size did not influence the amount adsorbed. For continuous adsorption system fixed to the bed height 17 cm and the flow rate was varied in the system 2,0; 4,0 and 8,0 mL/min. The results showed that the flow rate of 2,0 mL/min was the one with the lowest values of bed height unused. The effluent after treatment combination of coagulation/flocculation/sedimentation of membrane separation and adsorption, the best process conditions studied, showed high removals of the parameters studied, with most within the standards of quality of water used in the laundry.